Towards a model of translation revision competence. Issue 1 (2nd January 2017) - Robert, Isabelle S.; Remael, Aline; Ureel, Jim J.J.
ABSTRACT: Compared with research into translation competence (TC), which has been on the increase and has seen rapid developments since the 1990s, research into translation revision competence (TRC) is much newer and less developed as a major line of investigation. The aim of this article is (1) to construct a provisional TRC model, and (2) to provide concrete ideas for (empirical) studies into the validation of this model. The underlying hypothesis is that TC and TRC share some characteristics, but differ in several ways. First, the concepts of translation revision and competence are discussed and operationalised. Subsequently, a hypothetical model of TRC is presented using features from three existing models of TC (PACTE, TransComp, EMT expert group) and combining relevant TC insights provided by those models with three TRC-specific features: translation experience, interpersonal attitude and the ability to justify textual changes. The presentation of the TRC model is followed by a brief exploration of the four hypotheses on which it draws. Finally, concrete suggestions for further empirical research into the presented TRC model are discussed, with a view to advancing valid and reliable approaches to investigating the construct of TRC.